The rate of missed diagnosis of lower-limb DVT by ultrasound amounts to 50% or so in patients without symptoms of DVT: A meta-analysis. Issue 37 (September 2019) - Zhang, Yuhong; Xia, Haifa; Wang, Yaxin; Chen, Lin; Li, Shengnan; Hussein, Idrees Ali; Wu, Yan; Shang, You; Yao, Shanglong; Du, Ruofei
Abstract: Background: To assess whether the ultrasound (US) is a reliable approach in detecting lower-limb deep-vein thrombosis (DVT) in patients without symptoms of DVT. Methods: The research team performed a systematic search in PubMed, Ovid, Cochrane, and Web of Science without language or date restrictions. Full-text reports on prospective diagnostic studies involve the detection of lower-limb proximal and distal DVT in patients without symptoms of DVT using US and venography. A meta-analysis was performed using Meta-DiSc (version 1.4), providing the pooled sensitivity, specificity, positive (LR+) and negative (LR–) likelihood ratios of the detection accuracy of US. There were 4 different classes of subgroup analysis—the class of patients stratified by location of US exam (proximal, distal, whole leg), the class stratified by technique (color/doppler, compression, both modalities), the class stratified by kind of surgery (orthopedic, otherwise hospitalized) and the class stratified by era of publishing (1980s, 1990s, 2000s). The study quality and the risk of bias were evaluated using QUADAS-2, with heterogeneity was assessed and quantified by the Q score and I 2 statistics, respectively. Results: The meta-analysis included 26 articles containing 41 individual studies with a total of 3951 patients without symptoms of DVT. Using venography as the gold standard, US for proximal DVT had a pooled sensitivity of 59% (95% confidence interval (CI) = 51%–66%) and a pooled specificity of 98% (95% CI = 97%–98%), US for distal DVT had a poor sensitivity of 43% (95% CI = 38%–48%) and a pooled specificity of 95% (95% CI = 94%–96%), US for whole-leg DVT had a pooled sensitivity of 59% (95% CI = 54%–64%) and a pooled specificity of 95% (95% CI = 94%–96%), US for post-major orthopedic surgery patients had a pooled sensitivity of 52% (95% CI = 49%–55%), and US for other types of patients had a pooled sensitivity of 58% (95% CI = 43%–72%). Pure compression technique for DVT had a poor sensitivity of 43% (95% CI = 39%–48%), pure color/doppler technique for DVT had a pooled sensitivity of 58% (95% CI = 53%–63%), compression and color/doppler technique for DVT had a pooled sensitivity of 61% (95% CI = 48%–74%). Conclusion: US could be a useful tool for diagnosing DVT, but it has a lower positive rate and a higher false negative rate. The rate of missed diagnosis of lower-limb DVT by US amounts to 50% or so in the patients without symptoms of DVT. The negative results do not preclude the possibility of DVT and if appropriate heightened surveillance and continued monitoring or try a more accurate inspection method is warranted. The whole leg evaluation and color/doppler technique should be the preferred approach.